A highly enhanced photoelectrochemical performance of BiVO4 photoanodes modified with CoPi groups by increasing energy band bending, accelerating hole separation and improving water oxidation kinetics. Issue 4 (19th January 2022) - Fang, Wanqing; Qin, Ai; Lin, Yimin; Xv, Rongzi; Fu, Li
Abstract : Co-Pi has a synergistic effect on the photoelectrochemical water oxidation of the BiVO4 photoanode: increasing energy band bending, accelerating the hole separation and acting as an oxygen evolution co-catalyst with faster water oxidation kinetics. Abstract : BiVO4 is one of the most attractive photoanode materials for photoelectrochemical water splitting. Herein, a cobalt phosphate (CoPi) modified BiVO4 (BiVO4 /CoPi) photoanode is prepared by electrodeposition. The physical and chemical characterization shows that the BiVO4 /CoPi photoanode has a three-dimensional porous structure formed by the aggregation of nanoparticles. Amorphous CoPi is successfully deposited on the surface of BiVO4 . The photocurrent density of BiVO4 /CoPi increases to 5.87 mA cm −2 at 1.23 VRHE (3.24 times that of BiVO4 ). Based on the law of conservation of energy, it can be inferred that CoPi acts as an effective co-catalyst to reduce the activation energy ( E a ) of the oxygen evolution reaction. The chopping current density–time curve indicates that CoPi, as a hole extractor, can reduce the charge accumulation on the BiVO4 surface. The Mott–Schottky curve shows that CoPi increases the band bending of BiVO4 . It can be found that the applied bias photon-to-current efficiency (ABPE), charge separation efficiency ( η sep ) and charge injection efficiency ( η inj ) of BiVO4 /Co-Pi are enhanced. This is attributed to the synergistic effect of CoPi: increasing energy band bending, accelerating the hole separation and acting as an oxygen evolution co-catalyst with faster water oxidation kinetics. This work may provide new insights into the comprehensive effects of CoPi on the photoelectrochemical water oxidation of the BiVO4 photoanode.